State Education Agency Planning and Federally Funded Programs Perceptions of Selected Groups. Report of a Special Study - Milstein, Mike M.; Improving State Leadership in Education, Denver, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This document presents the results of a survey of selected groups concerning (1) the influence of federally funded programs on planning and planning related activities of State education agencies, and (2) the reactions of State education agencies to their responsibilities relative to federally funded programs. Responses indicated that federally funded education programs have often caused major changes in educational governing structures with consequent disruptions of planning activities. The authors conclude that planning performance in State education agencies could be improved by improving relations and communications with the Federal Government and by pursuing planning at the highest organizational levels in the agencies. (RA)
Availability: Improving State Leadership in Education, 1362 Lincoln Street, Denver, Colorado 80203 (Single copies free).
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Cooperation; Cooperative Planning; Federal Aid; Federal Programs; Federal State Relationship; Planning; Program Administration; State Agencies; State Departments of Education; State Federal Aid; Statewide Planning; Surveys; Elementary Secondary Education Act Title V